2014
DOI: 10.4236/fns.2014.59090
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Oxidative, Anti-Hyperglycemic and Lipid-Lowering Effects of Aqueous Extracts of <i>Ocimum sanctum</i> L. Leaves in Diabetic Rats

Abstract: The present study was conducted to investigate the effect of aqueous extracts of Ocimum sanctum L. leaves on blood glucose, serum lipid profile and anti-oxidative activity to protect various risk organs in DM rats. Ocimum sanctum L. leaves were extracted using water, then the total phenolic content was determined. Three groups of male Wistar rats were used including normal control rats, DM rats and DM rats daily fed with aqueous extracts of Ocimum sanctum L. leaves (AQOS) for three weeks. DM rats were induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Our previous study showed that a diet containing 2% OS leaf powder resulted in a significant reduction in blood glucose levels in streptozotocin-induced DM rats ( 14 ). The administration of aqueous and alcoholic extracts of OS leaves also resulted in reduced blood glucose levels in streptozotocin-induced DM rats ( 15 , 16 ), and prevented insulin resistance in normal rats fed with a fructose diet ( 17 ). Prior studies have suggested that OS leaf extracts possess anti-hyperglycemic activity, in addition to protecting organs against various stress conditions such as hyperlipidemia ( 6 ), inflammation ( 18 ), cancer ( 19 ) and heavy metal toxicity ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our previous study showed that a diet containing 2% OS leaf powder resulted in a significant reduction in blood glucose levels in streptozotocin-induced DM rats ( 14 ). The administration of aqueous and alcoholic extracts of OS leaves also resulted in reduced blood glucose levels in streptozotocin-induced DM rats ( 15 , 16 ), and prevented insulin resistance in normal rats fed with a fructose diet ( 17 ). Prior studies have suggested that OS leaf extracts possess anti-hyperglycemic activity, in addition to protecting organs against various stress conditions such as hyperlipidemia ( 6 ), inflammation ( 18 ), cancer ( 19 ) and heavy metal toxicity ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 96%
“…Prior studies have suggested that OS leaf extracts possess anti-hyperglycemic activity, in addition to protecting organs against various stress conditions such as hyperlipidemia ( 6 ), inflammation ( 18 ), cancer ( 19 ) and heavy metal toxicity ( 20 , 21 ). Furthermore, an aqueous extract of OS leaves has been shown to promote antioxidative activity, thus protecting various organs against DM ( 16 , 22 ). OS leaves are known to be a rich source of volatile and fixed oils.…”
Section: Introductionmentioning
confidence: 99%
“…Tulsi exhibits antidiabetic activity, as was revealed in one study, it was observed that aqueous extract of Tulsi significantly lowers the blood glucose level in diabetic rats [8,79]. Similarly, other studies also confirm a fall of fasting blood sugar level and HBA1c was also contributed by the hypoglycemic effect of Tulsi [80,81].…”
Section: Antidiabetic Activitymentioning
confidence: 56%
“…Available potassium (K) concentration was determined using 1 M Ammonium Acetate. Particle-size distribution was determined by the hydrometer method (Kruma et al, 2008;Suanarunsawat et al, 2014). The experiment was conducted in a factorial randomized complete design with three replications.…”
Section: Methodsmentioning
confidence: 99%